Mechanisms of mechanical force in periodontal homeostasis: a review - Wang, Tianqi; Liu, Xinran; Li, Jiaxin; Yue, Yuan; Li, Jinle; Wang, Min; Wei, Na; Hao, Liang (Frontiers in Immunology, 2024)
Mechanical forces affect periodontal health through multiple mechanisms. Normally, mechanical forces can boost soft and hard tissue metabolism. However, excessive forces may damage the periodontium or result in irreversible inflammation, whereas absence of occlusion forces also leads to tissue atrophy and bone resorption. We systemically searched the PubMed and Web of Science databases and found certain mechanisms of mechanical forces on immune defence, ECM metabolism, specific proteins, bone metabolism, characteristic periodontal ligament stem cells (PDLSCs) and noncoding RNAs (ncRNAs) as these factors contribute to periodontal homeostasis. The immune defence functions change under forces; genes, signalling pathways and proteinases are altered under forces to regulate ECM metabolism; several specific proteins are separately discussed due to their important functions in mechanotransduction and tissue metabolism. Functions of osteocytes, osteoblasts, and osteoclasts are activated to maintain bone homeostasis. Additionally, ncRNAs have the potential to influence gene expression and thereby, modify tissue metabolism. This review summarizes all these mechanisms of mechanical forces on periodontal homeostasis. Identifying the underlying causes, this review provides a new perspective of the mechanisms of force on periodontal health and guides for some new research directions of periodontal homeostasis.